Analisis Pengungkapan Tata Kelola Syariah pada Perbankan Syariah Indonesia, Malaysia dan Bahrain - Jannah, Suci Ashabal; Meutia, Inten; Syahtiri, Ahmad (Universitas Muhammadiyah Jakarta, 2024)
Objectives: This study aims to test and analyze the effect of sharia supervisory board size, sharia supervisory board expertise, sharia supervisory board meetings, audit committee size, audit committee expertise, audit committee meetings, and CEO duality on shari'ah corporate governance in 15 Islamic banks in Indonesia, Malaysia and Bahrain during the period 2013-2022.Design/method/approach: The analysis technique in this study is quantitative with multiple regression analysis tools with a panel data approach Results/findings: The results of this study are (1) supervisory board expertise and meetings have a significant effect on shari'ah corporate governance disclosure (2) supervisory board size, audit committee size, meetings. expertise and CEO duality have an insignificant effect on shari'ah corporate governance disclosureTheoretical contribution: The application of Stewardship Theory to the disclosure of Shari'ah Corporate Governance as well as expanding insight and literature on Shari'ah Corporate Governance, Shari'ah Corporate Governance regulations, and the application of standards used by Islamic banking in several countries.Practical contribution: As a reference for regulators related to Shari'ah Corporate Governance to improve the quality of the standards that have been set.Limitations: The research object is only carried out in three countries, namely Indonesia, Malaysia and Bahrain so that the sample studied is still small